28‐2: A Novel Local Dimming algorithm with HDR for VR system based on GPU. Issue 1 (29th May 2019) - Ji, Zhihua; Li, Wenyu; Shi, Tiankuo; Zhang, Xiaomang; Sun, YuKun; Miao, JingHua; Shi, Lingyun; Duan, Xin
Abstract : As the screen of VR is very close to human eye and the optical lens has amplification effect, VR needs high PPI to meet people's visual requirements. High PPI panel with side‐emitting LED backlight is difficult to realize high contrast ratio(CR). Local Dimming based on direct‐illumination LED can not only save backlight power consumption but also improve the CR of the VR system. The point spread function(PSF) of LED plays an important role in Local Dimming technology. However traditional PSF always adopts approximate calculation method with low accuracy, which causes luminance distortion. In this paper, a method of PSF measurement and data processing was proposed. It can describe the spread strength and range of one single block LED actually. One improved LCD compensation algorithm was demonstrated in this paper. The light leakage characteristic of liquid crystal was considered. It can keep the hue consistent. The proposed Local Dimming method has low distortion and high dynamic contrast range. This paper also presents a method for implementing Local Dimming algorithm by GPU, which can display Local Dimming effect in real time of VR system with high frame rate.